2020
DOI: 10.1186/s40104-020-00492-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protocatechuic acid ameliorates inflammation and up-regulates intestinal tight junction proteins by modulating gut microbiota in LPS-challenged piglets

Abstract: Background Weaning is one of the major factors that cause stress and intestinal disease in piglets. Protocatechuic acid (PCA) is an active plant phenolic acid which exists in Chinese herb, Duzhong (Eucommia ulmoides Oliver), and is also considered as the main bioactive metabolite of polyphenol against oxidative stress and inflammation. This study aimed to investigate the effect of PCA on growth performance, intestinal barrier function, and gut microbiota in a weaned piglet model challenged with lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 45 publications
8
113
0
Order By: Relevance
“…The reported studies revealed an elevated expression level of proinflammatory cytokines in patients affected with IBD, which implied that targeting the balance between proinflammatory and anti-inflammatory cytokines could be a potential treatment for gut inflammation [47]. In the current study, the obtained results indicated that LPS stimulation not only enhanced the mRNA expression of IL-6 and IL-1β but also enhanced the transcriptional and translational level of iNOS, and further induced intestinal inflammation, which showed consistency with the other reported studies [48,49]. Some studies revealed that gut immunity has been considerably associated with gut microbiota [4,5], and a wide range of gastrointestinal diseases, such as recurrent C. difficile infection (CDI), inflammatory bowel diseases (IBD, including Crohn's disease (CD) and ulcerative colitis (UC)), colorectal cancer (CRC), and metabolic disorders, are affected by the variations observed in the composition and functions of gut microbiota [6,50].…”
Section: Discussionsupporting
confidence: 90%
“…The reported studies revealed an elevated expression level of proinflammatory cytokines in patients affected with IBD, which implied that targeting the balance between proinflammatory and anti-inflammatory cytokines could be a potential treatment for gut inflammation [47]. In the current study, the obtained results indicated that LPS stimulation not only enhanced the mRNA expression of IL-6 and IL-1β but also enhanced the transcriptional and translational level of iNOS, and further induced intestinal inflammation, which showed consistency with the other reported studies [48,49]. Some studies revealed that gut immunity has been considerably associated with gut microbiota [4,5], and a wide range of gastrointestinal diseases, such as recurrent C. difficile infection (CDI), inflammatory bowel diseases (IBD, including Crohn's disease (CD) and ulcerative colitis (UC)), colorectal cancer (CRC), and metabolic disorders, are affected by the variations observed in the composition and functions of gut microbiota [6,50].…”
Section: Discussionsupporting
confidence: 90%
“…The interaction between polyphenols including their metabolites and gut microbiota is critical to understanding the biological mechanisms of polyphenols, since polyphenols are poorly absorbed and most of them are metabolized by the microbiome to form phenolic metabolites ( 40 ). Dietary polyphenols could play a key role in growth of several beneficial bacteria including Lactobacillus and Bifidobacterium spp .…”
Section: Interaction Between Dietary Polyphenols and Gut Microbiomementioning
confidence: 99%
“…Lachnospiraceae and Ruminococcaceae are closely related to the production of butyrate (31,32). Prevotellaceae UCG-001 belongs to the family of Prevotellace showed a positive correlation with the expression of inflammatory factors in our recent study (33). Sutterella is positively correlated with neutral detergent fiber (NDF) digestibility (34), and Bilophila has a positive correlation with obesity-related markers (18), while Sedimentibacter can secrete cellulase enzyme to digest cellulose into glucose (19,34).…”
Section: Discussionmentioning
confidence: 79%